Flexibility of C3h‐Symmetrical Linkers in Tris‐oligonucleotide‐Based Tetrahedral Scaffolds. Issue 3 (17th December 2015) - Panagiotidis, Christos; Kath‐Schorr, Stephanie; von Kiedrowski, Günter
Abstract: Flexibility of tris‐oligonucleotides is determined by the length of their connecting hydrocarbon chains. Tris‐oligonucleotides are branched DNA building blocks with three oligonucleotide arms attached to a C 3 h ‐symmetrical linker core at these chains. Four tris‐oligonucleotides hybridise into a tetrahedral nanocage by sequence‐determined self‐assembly. The influence of methylene, ethylene and propylene chains was studied by synthesising sets of tris‐oligonucleotides and analysing the relative stability of the hybridisation products against digestion by mung bean nuclease by using gel electrophoresis. Linkers with ethylene chains showed sufficient flexibility, whereas methylene‐chain linkers were too rigid. Tris‐oligonucleotides based on the latter still formed tetrahedral scaffolds in intermixing experiments with linkers of higher flexibility. Thus, a new generation of versatile isocyanurate‐based linkers was established. Abstract : Tweaking tiny tetrahedrons : Tris‐oligonucleotide flexibility is determined by hydrocarbon chains at the linker core, which allow a set of four tris‐oligonucleotides to fold into a tetrahedral nanocage. So far, the feasibility of methylene and ethylene chains is unexplored. A new generation of isocyanurate‐based linkers was developed to offer easier and facile access to tris‐oligonucleotides.